2022
DOI: 10.3389/fpls.2022.999433
|View full text |Cite
|
Sign up to set email alerts
|

An efficient Agrobacterium-mediated transient transformation system and its application in gene function elucidation in Paeonia lactiflora Pall

Abstract: Paeonia lactiflora Pall. is known as the king of herbaceous flowers with high ornamental and precious medicinal value. However, the lack of a stable genetic transformation system has greatly affected the research of gene function in P. lactiflora. The Agrobacterium-mediated transient gene expression is a powerful tool for the characterization of gene function in plants. In this study, the seedlings of P. lactiflora were used as the transformation receptor materials, and the efficient transient transformation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…found that there was no significant change in the expression of the gene after co-culturing young leaves of Populus alba for 3-5 days ( Song et al., 2019 ). We found in the experiment that the transformation efficiency of L. caerulea was stable after co-cultivation for 3-6 days, which is similar to previous research results ( Guan et al., 2022 ; Wu et al., 2022 ). The culture medium and co-transformation time used in this study differ slightly from the experimental methods used in the previous article due to the different plant materials, but the above transient genetic transformation systems achieved the goal of quickly identifying gene function and the regulatory relationship between genes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…found that there was no significant change in the expression of the gene after co-culturing young leaves of Populus alba for 3-5 days ( Song et al., 2019 ). We found in the experiment that the transformation efficiency of L. caerulea was stable after co-cultivation for 3-6 days, which is similar to previous research results ( Guan et al., 2022 ; Wu et al., 2022 ). The culture medium and co-transformation time used in this study differ slightly from the experimental methods used in the previous article due to the different plant materials, but the above transient genetic transformation systems achieved the goal of quickly identifying gene function and the regulatory relationship between genes.…”
Section: Discussionsupporting
confidence: 91%
“…If the infection time is too long, it will cause the explants to suffer from hypoxia and decay due to the toxicity of Agrobacterium ; The short duration of infection prevents successful transformation. The optimal conversion time for transient transformation of Paeonia lactiflora is 12 h ( Guan et al., 2022 ). The optimal time for transient transformation of lilies ( Lilium longiflorum ) is 5 h ( Wu et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other transient transformation methods, such as biolistic transformation and syringe infiltration, it is simple, quick, economical, and effective. In the last decade, the function of a growing number of genes in Tamarix hispida , Betula platyphylla, Morus alba , Populus trichocarpa , Withania somnifera and Paeonia lactiflora have been identified using this full seedlings soaking transient transformation method [ 15 17 , 21 , 30 , 43 , 46 , 49 , 54 , 58 , 71 , 72 , 74 ]. It also facilitates research on regulatory networks [ 23 , 24 , 59 , 65 ] and reverse chromatin immunoprecipitation technique [ 54 , 58 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research focusing on the construction of the VIGS system yielded optimal results and shed light on the transient transformation in geophytes [56,57]. Inspired by the cormlet and bulblet used as materials for VIGS to investigate gene regulation in bud growth transitions and corms dormancy in bulbous flowers, we established a homologous silencing system with intact-plant infiltration and minimized operation based on a prior study on VIGS system construction in herbaceous and tree peonies [44,58,59]. This established methodology is also applicable to more than 30 species of herbaceous peonies and can provide a valuable reference for all other geophytes.…”
Section: The Established Vigs System Is Suitable For Gene Function Re...mentioning
confidence: 99%